Gender Bias in the Representation of Historical Figures: Evidence from Pre-Service Primary Teachers: Gender Bias in the Representation of Historical Figures: Evidence from Pre-Service Primary Teachers - Ortuño Molina, Jorge; Ibáñez-López, Francisco Javier; Molina Puche, Sebastián (Revista Complutense de Educación, 2026)
Understanding how future teachers interpret historical figures is essential for addressing gender bias in history education. This study examines gender-based differences in the attribution of values to historical figures among pre-service primary teachers. A quantitative, non-experimental design was employed with a sample of 662 students from eight Spanish universities. Results indicate that self-promotion values are predominant regardless of gender, reflecting a politicized view of history. However, female historical figures are more frequently associated with collective and care-oriented values. These findings reveal the persistence of gendered cultural representations in historical understanding and highlight the role of teacher education in challenging implicit biases. The study contributes to research on history education by linking value attribution to broader debates on gender, culture, and educational practice.